Effect of Stock Split on Abnormal Return, Trading Volume Activity, Stock Price, Bid-Ask Spread, and Systematic Risk of Companies - Hery Haryanto; Lina Lina (University of Merdeka Malang, 2023)
Go-public companies can use various techniques and strategies to collect capital for their companies. One of them is by carrying out corporate actions. Stock Split is a company strategy that increases the liquidity of a stock by breaking it into several shares. This study was conducted to see the effect of stock split on whether there were differences in abnormal returns, trading volume activity, stock price, bid-ask spread, and systematic risk at companies that conducted stock split in the 2018-2020 period. A total of 40 companies registered on the IDX and conducted stock split from 2018-2022 to be selected samples using the purposive sampling method. In data processing, software-based technology is used SPSS 25. Based on the calculation and results of data analysis, there are differences in the abnormal return variable before and after the stock split is carried out. While other variables, namely trading volume activity, stock price, bid-ask spread, and systematic risk, no difference between before and after stock split is carried out by the company.